The telephone and its uses - Linscott, Frank Mallett (My University, 1891)
Introduction: The invention of a device by means of which the exact tones and inflections of the human voice are transmitted to a distant station constitutes the most valuable step of advancement in the progress of telegraphical communication. While the growth of the “telephone” has been accompanied by a number of outbreaks in its march, yet its growth has been one of comparative steadiness, and not as many would have you to believe the work of but little more than a decade. As the existence of sound is due to the vibration of surrounding mediums, the object to be accomplished was to contrive suitable means by which vibrations could be set up inspective of the distance from which they originated.
Citation: Linscott, Frank Mallett. The telephone and its uses. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Telephone; Invention; Telegraphy; Theses; Manuscripts (documents)